Digital Marketing Strategy on Increasing Transaction Volume in MSMEs in the Post-Pandemic Era - Sri Wahyuni (Pusat Riset dan Inovasi Nasional, 2024)
The accelerated digital transformation due to the COVID-19 pandemic has driven Micro, Small, and Medium Enterprises (MSMEs) to adopt digital marketing strategies to sustain their businesses and increase sales transactions. This study aims to analyze the influence of digital marketing strategies on the increase in transaction volume among MSMEs in the post-pandemic era. A quantitative research method was employed using a survey approach. Data were collected through questionnaires distributed to 100 MSME actors in West Java who actively utilize digital platforms. Multiple linear regression analysis was used to examine the influence of variables such as social media usage, paid advertising, and Search Engine Optimization (SEO) on transaction volume. The results of the study indicate that digital marketing strategies have a positive and significant impact on the increase in MSME transaction volume. Social media is the most dominant component in driving consumer engagement and transaction conversion. These findings emphasize the critical role of digital marketing as a primary tool for business recovery and development in the digital era. The study recommends improving digital literacy and providing strategic mentoring to enable MSMEs to manage digital marketing more effectively.